Sony applicant recruitment system using fuzzy logic / Nik Zurifa Nabilah Zulkifli - Zulkifli, Nik Zurifa Nabilah (2022)
Fuzzy Logic algorithms have adapted to fit a wide range of uses. Hundreds of methodologies have been applied, with even minor changes on current approaches spawning new study fields. This study conducts a thorough assessment of typical Fuzzy Logic approaches, considers their benefits and drawbacks, and discusses how their typical uses connect to their respective pros and cons. This research of Fuzzy Logic approaches provides a clear direction for how Fuzzy Logic methods should be applied in specific scenarios. The allocation of employees is a criteria evaluation choice with strategic implications for many organizations as they are currently dealing with a great deal of pressure and difficulty in obtaining insightful and qualified employee. The traditional procedures for selecting employees are insufficient to handle with the imprecise or ambiguous character of language assessment. Fuzzy Logic approach are presented as a solution to this problem. The conceptual model is designed to analyze a few candidates predicated on their resumes before ranking them based on the company's recruitment strategy and workforce requirement. One employing method from the human resource management literature is used to attain the research's goal: Job-Fit Recruiting—finding individuals who are most suited with a given positional criterion. The purpose of this research is to apply the Fuzzy Logic approach to select candidates in companies. A real criteria position in Sony is used to validate the suggested paradigm. The suggested methodologies were used to solve candidates screening in Sony involving the allocation of Web Designers position. After establishing the criteria that influence Web Designers' selections, the problem is solved using fuzzy logic approaches, and the findings are reported. Google’s website called colab.research.google.com was used to create the system.